Stenocarpella spp. inoculum quantification in tropical maize stubble - Pinto, Felipe Augusto Moretti Ferreira (2016)
Stenocarpella species (S.maydis and S.macrospora) overwinters in maize stubble and no-till monoculture maize is related to ear and stalk rot outbreaks, but little is known about the factors that contribute to its survival. Therefore this work aimed at determining the contribution of soybean crop rotation and fallow land on pathogen survival and dynamics of maize stubble breakdown, and determining factors that contribute to the pathogens survival. Inn the first article maize fields with history of severe white ear rot were used to determine the stubble sampling size to analyze the pathogen sporulation and viability, as well the maize decomposition. The maize monoculture was compared to one round of soybean rotation and fallow. In the second article, maize fields were selected in the maize growing areas in the state of Minas Gerais for sampling maize stubbles. During the offseason, maize stalks, grains, cobs, fallen maize leaves, straw and dead weed stubble were collected. During the 2015/16 season stalks and cobs were collected in areas under conventional tillage, no-tillage, either with crop rotation or maize monoculture. Samples were processed, freeze-dried, powedered, had their DNA extracted and the Stenocarpella sp inoculum quantified through qPCR. Soils from the sampled fields were checked for suppressivity to ear and stalk rot -causing fungi. Heat maps were generated with the obtained data. A sub-sample of one kilogram was the minimum necessary to estimate the pathogen survival. The pathogen sporulation was similar among treatments but viability was reduced (27.8-33.3%) in the considered regions. The stubble decomposition was higher in only one location. The sample size, classical and molecular methods allowed the survey of the pathogen in maize stubble and pointed out the role of soybean crop rotation in the reduction of Stenocarpella sp viability. In cultivated areas adopting the conventional tillage system, the pathogen was not detected. However, under no-tillage managed areas, Stenocarpella sp was detected to a lesser extent than in areas adopting no-tillage system with maize monoculture. The results endorse the role of maize stubbles in the survival of Stenocarpella sp. and crop rotation as a useful method to manage the diseases caused by Stenocarpella maydis.